Experimental Study and Performance Analysis of a Recuperative Supercritical CO2 Brayton Cycle - Shucheng Zhang; Juntao Ke; Min Liu; Pingjian Ming; Guopeng Yu (Energies)
To investigate the operational characteristics of the supercritical carbon dioxide (S-CO2) Brayton cycle and enhance its applicability in practical operating conditions for micro-scale reactors, an experimental platform for a recuperative S-CO2 Brayton cycle is constructed and investigated. Several controllable operational parameters, including compressor pump frequency, expansion valve opening, and electric heating power, each intrinsically linked to the thermal characteristics of its corresponding equipment, as well as the cooling water flow rate, are systematically adjusted and analyzed. Experimental results demonstrate that the cooling water flow rate has a significantly greater impact on the temperature and pressure of the cycle system compared to other operational parameters. Based on these findings, steady-state experiments are conducted within a pressure range of 8 MPa to 15 MPa and a temperature range of 70 °C to 150 °C. It is observed that the heat exchange capacity of the recuperator decreases as the cooling water flow rate is reduced, suggesting that sufficient cooling efficiency is required to maximize the recuperative function. Under the condition of a maximum system temperature of 150 °C, the isentropic efficiency of the expansion valve decreases with an increase in the inlet pressure of the valve. However, the overall thermal efficiency of the cycle system requires further calculation and assessment following the optimization of the experimental platform. The result of validation of experimental results is less than 20%. The findings presented in this study offer essential data that encompass the potential operational conditions of the CO2 Brayton cycle section applicable to small-scale reactors, thereby providing a valuable reference for the design and operation of practical cycle systems.